Commitment of Generation Z Employees – Diagnosis, Expectations, and Courses of Action - Borowska, Magdalena; Pietroń-Pyszczek, Agata (Zaangażowanie pracowników pokolenia Z − diagnoza, oczekiwania, kierunki działań, 2025)
Aim: The aim of the article was to determine the level of engagement of Generation Z and to indicate directions for actions aimed at consciously shaping it within the organisation. Methodology: A literature review and analysis of the results of a survey among students of the Wroclaw University of Economics and Business were conducted. The study was based on a typology of commitment: to the organisation, work, profession, and supervisor. Results: The respondents declared a high level of commitment. The largest percentage of the respondents declared commitment to their work, followed by commitment to their supervisor, while commitment to the organisation received the lowest percentage of responses. Women were more likely to indicate commitment to their work and profession; men were more attached to their superiors. Implications and recommendations: Organisations should support engagement through mentoring, employee participation in management, and promoting social and environmental responsibility. It is important to create incentive systems that reward environmental activity, which can support the integration of young employees with the company's mission. Originality/value: The engagement model used allows for comprehensive assessment of Generation Z preferences in terms of attachment to the organisation, their work, their profession, and their supervisor. It also enabled the identification of key motivational factors in these areas that support the engagement of young employees, allowing for the design of effective management measures.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 24-37